Volkskirchen in Deutschland im gesellschaftlichen Wandel - Manderscheid, Michael; Tröndle, Corinna (European Journal of Mental Health, 2008)
People’s Churches in Germany in the Midst of Social Changes: In times prior to the modern age church and society more or less formed a unit; however, with the advent of the modern age a process of shutting out the church from the public sphere started. In the flourishing modern age a differentiated society was formed, in which social subsystems coexisted. The church and religion lost their former power of interpretation, and traditional social environments close to the church also disappeared. The process of individualisation was also manifested in the setback to church membership. In the post-modern society the pluralisation of lifestyles further increased. The concept of experience society touches on the essence of post-modern society, in which aesthetics and lifestyles play an increasing role. Traditional points of view do not sufficiently take such complex social relations into consideration. In addition to socio-economic living conditions, models such as Sinus-Milieus also focus on value orientations, lifestyles and aesthetic preferences. Attachment to the dissolving traditional social environment is a danger to the future of churches in Western Europe. In order to have a future in a post-modern milieu society, mental health care professionals need to reflect, decide and experiment with how they want to address people with diverse backgrounds, following the example of Paul the Apostle (1 Cor 9:19–23), and how they can succeed in doing so. Discussions related to the milieus outlined here provide connection points for this.